The lightning thief - Riordan, Rick. (New York : Disney/Hyperion Paperbacks for Children, 2006)
After learning that he is the son of a mortal woman and Poseidon, god of the sea, twelve-year-old Percy is sent to a summer camp for demigods like himself, and joins his new friends on a quest to prevent a war between the gods.
I accidentally vaporize my pre-algebra teacher -- Three old ladies knit the socks of death -- Grover unexpectedly loses his pants -- My mother teaches me bullfighting -- I play pinochle with a horse -- I become supreme lord of the bathroom -- My dinner goes up in smoke -- We capture a flag -- I am offered a quest -- I ruin a perfectly good bus -- We visit the Garden Gnome Emporium -- We get advice from a poodle -- I plunge to my death -- I become a known fugitive -- God buys us cheeseburgers -- We take a zebra to Vegas -- We shop for water beds -- Annabeth does obedience school -- We find out the truth, sort of -- I battle my jerk relative -- I settle my tab -- Prophecy comes true.
Keywords: Jackson, Percy (Fictitious character) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Poseidon (Greek deity) -- Juvenile fiction; Hades (Greek deity) -- Juvenile fiction; Zeus (Greek deity) -- Juvenile fiction; Fantasy fiction